The need for the approval of the INPI for approval of an agreement between plaintiff and defendant in trademark nullity actions, patents and industrial designs (Revista do Tribunal Regional Federal da 3ª Região, 2013)
The article aims to demonstrate that, once a lawsuit has been filed to declare a patent, trademark or industrial design null and void, the plaintiff is unable to negotiate with the defendant who owns the contested asset to drop the lawsuit without the National Institute of Industrial Property's agreement. Based on a historical analysis of the legislation, a case study and a systematic-teleological interpretation, the study argues that the opposition of the state entity to the agreement, in cases where it believes there is nullity, in order to proceed with the action, is supported by society's interest in making exclusivity rights null and void and improving the industrial property protection system, with repercussions on free competition, the guarantee of exempt consumer choice and the country's economic and technological development.
Keywords: agreement; homologation; nullity action; trademarks; patents; industrial designs; withdrawal